Housing Market Dynamics: New Insights from the Indicator Approach - Zhi-Cheng, Voon; Chin-Hong, Puah; Abu Mansor, Shazali (2016)
The housing market and financial stability are inextricably linked. Indeed, insights on housing market risks can influence the financial stability of a country or region, passing critical impacts to the real economy as a whole. Therefore, the purpose of the present study is to model the oscillations of the housing market to explain and predict the boom-bust patterns in the housing cycle. We focus on the shifts in the fundamental driving forces of the housing cycle that are anticipated by a set of macro and micro foundations of housing behaviors. We explore the possibility that the waves in the housing market can be captured in information needed for policy planning, risk monitoring, and community development, as well as the delivery of affordable housing. In this context, a non-parametric indicator construction framework inspired by the National Bureau of Economic Research (NBER) of the United States was applied to develop the housing cycle indicator (HCI), with the aim of predicting the cyclical fluctuation in the housing market in the northern territory of Borneo Island. The constructed HCI correctly predicted the boom-bust patterns in the housing cycle and the average leading period was at best 9.75 months. The forward-looking attribute of the HCI suggests that it is a sound policy tool to foresee the housing market outlook in the near future.